XIIth International Symposium for Biomechanics and Medicine in Swimming (Australian Institute of Sport, 2014)
The BMS2014 Book of Proceedings contains more than 100 full papers relating to presentations given at the symposium. It includes either full papers or the presentation slides of many of the keynote speakers. The main contents of the articles are: - biomechanics, - coaching, - computational fluid dynamics, - medicine, - Physiology, - physiotherapiy, - social sciences, humanities and pedagogics.